THE INFLUENCE OF ENVIRONMENTAL REGULATION ON CORPORATE ENVIRONMENTAL DISCLOSURE: THE MODERATING ROLE OF CORPORATE GOVERNANCE - Wang , Shiyi; Lau , Lin Sea; Lee, Ah Suat (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Corporate environmental information carries significant social externalities, necessitating effective environmental regulation to guide and standardize disclosure practices. Drawing on stakeholder theory, legitimacy theory, and agency theory, this study examines the impact of environmental regulation—perceived by corporates within the regulatory framework—on corporate environmental disclosure while also investigating the moderating role of corporate governance. Based on a panel dataset of 327 listed pharmaceutical companies in China, covering the period from 2018 to 2022, this study employs fixed effects regression analysis to test these relationships empirically. The Generalized Method of Moments (GMM) regression is also applied as a robustness check to address potential endogeneity concerns. The results indicate that intensified environmental regulation significantly promotes corporate environmental disclosure among Chinese pharmaceutical firms. Furthermore, corporate governance is found to positively moderate this relationship, strengthening the effect of environmental regulation on disclosure practices. These findings offer important implications: policymakers should reinforce environmental regulation and improve enforcement mechanisms, while firms should enhance corporate governance structures to further improve their environmental disclosure performance.